Game : animals, videogames, and humanity - Tyler, Tom, 1968- (University of Minnesota Press, 2022)
"Video games conjure new worlds for those who play them, human or otherwise: they have been played by cats, pigs and penguins, and they let gamers experience life from the perspective of pets, predators, and prey. Tom Tyler's eclectic collection of essays considers a host of animals who challenge players to think anew about winning and losing, difficulty settings, accessibility, virtuality, vitality and vulnerability, and much more"--